Étudier l’appropriation des TIC à l’école en combinant l’examen des usages et des représentations sociales des utilisateurs. - Emmanuel BÉCHÉ (Tic & Société)
This article examines learners’ appropriation of Internet-connected computers in Yaoundé, Cameroon, through an analysis of their uses and social representations. This approach helps renew perspectives on social integration of ICTs, and is based on a double theoretical framework: the approach of appropriation and that of the central core. It uses three data collection methods: interview, network of association and direct observation. The analysis of uses highlights their contextualization, their symbolic value and the role of learners in appropriating the technology. That of social representation brings out its content which is structured around the technical aspects of the tool, its features, and the value judgements towards it. For these learners, the central core of the Internet-connected computers is that of a technological device used mainly for school and communication activities. By translating the use of ICTs, the study of their social representations links it more to the dynamic process of their appropriation, whose content is revealed in several dimensions.